2021
DOI: 10.1002/ejoc.202100540
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Stereocontrolled Access Route to Piperidine or Azepane β‐Amino Esters and Azabicyclic β‐ and γ‐Lactams; Synthesis of Novel Functionalized Azaheterocyles

Abstract: An improved, efficient synthesis of some functionalized saturated azaheterocycles has been accomplished by controlled functionalization of various readily available cyclic compounds containing ring C=C bond. The stereocontrolled synthetic concept was based on the oxidative ring cleavage of various unsaturated scaffolds across ozonolysis followed by ring closing with double reductive amination with primary alkylamines or fluorinated alkylamines. The protocol provided versatile azaheterocyclic derivatives with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…The procedure was based on the oxidation of the C=C double bond into the corresponding dialdehydes by ozonolysis (Scheme 11). [20] In a previous work, [19a] the dihydroxylation/diol cleavage/ reductive amination protocol of the N-Boc-protected β-lactam (37) showed low reactivity under the conditions used (Scheme 10). In contrast, applying the ozonolysis/reductive amination procedure the reaction was more successful.…”
Section: Functionalizations Through the Oxidative Cleavage/ozonolysis...mentioning
confidence: 92%
See 3 more Smart Citations
“…The procedure was based on the oxidation of the C=C double bond into the corresponding dialdehydes by ozonolysis (Scheme 11). [20] In a previous work, [19a] the dihydroxylation/diol cleavage/ reductive amination protocol of the N-Boc-protected β-lactam (37) showed low reactivity under the conditions used (Scheme 10). In contrast, applying the ozonolysis/reductive amination procedure the reaction was more successful.…”
Section: Functionalizations Through the Oxidative Cleavage/ozonolysis...mentioning
confidence: 92%
“…purification was only necessary in the final step. [20] The ozonolysis/reductive amination method was performed with 2,2,2-trifluoroethylamine (Scheme 11). In contrast with the earlier work, [19] this reaction gave only two products: the known monocyclic diamino lactam 41 and piperidine-fused lactam 42 (Scheme 11).…”
Section: Functionalizations Through the Oxidative Cleavage/ozonolysis...mentioning
confidence: 99%
See 2 more Smart Citations
“…These compounds exhibit various biological activities, and they can also serve as building blocks of bioactive foldamers (Figure 2). [12][13][14] Our research group has reported a number of selective and controlled synthesis pathways toward azaheterocyclic -amino esters, 8,[15][16][17][18][19][20][21][22][23] including a recent stereocontrolled method that utilized an RRM of N-allylated (or N-propargylated) norbornene -amino esters to prepare compounds with a hexahydro-1H-cyclopenta[b]pyridine scaffold. 8 The current publication extends this pathway to provide access to further stereoisomers, namely, hexahydro-1H-cyclopenta[b]pyridine derivatives and some analogues with a hexahydrofuro [3,2-b]pyridine scaffold.…”
mentioning
confidence: 99%